Parental involvement on student academic achievement: A meta-analysis - Castro, María; Expósito Casas, Eva; López-Martín, Esther; Lizasoain, Luis; Navarro-Asencio, Enrique; Gaviria Soto, José Luis (Educational Research Review, 2017)
This paper is a quantitative synthesis of research into parental involvement and academic achievement through a meta-analysis of 37 studies in kindergarten, primary and secondary schools carried out between 2000 and 2013. Effect size estimations were obtained by transforming Fisher's correlation coefficient. An analysis has also been conducted of the heterogeneity of the magnitudes grouped according to different moderator variables, and a study of the publication bias affecting meta-analytical studies. The results show that the parental models most linked to high achievement are those focusing on general supervision of the children's learning activities. The strongest associations are found when the families have high academic expectations for their children, develop and maintain communication with them about school activities, and help them to develop reading, habits.(C) 2015 Elsevier Ltd. All rights reserved.
Keywords: parental involvement; parent participation; academic achievement; meta-analysis; JCR; Scopus